2015
DOI: 10.7554/elife.07902
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable roles of the inferior longitudinal fasciculus and fornix in face and place perception

Abstract: We tested a novel hypothesis, generated from representational accounts of medial temporal lobe (MTL) function, that the major white matter tracts converging on perirhinal cortex (PrC) and hippocampus (HC) would be differentially involved in face and scene perception, respectively. Diffusion tensor imaging was applied in healthy participants alongside an odd-one-out paradigm sensitive to PrC and HC lesions in animals and humans. Microstructure of inferior longitudinal fasciculus (ILF, connecting occipital and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 122 publications
(233 reference statements)
6
74
0
Order By: Relevance
“…The ILF pathway is generally considered a pathway through which information is conveyed from the extrastriate occipital cortex to the lateral temporal cortex, parahippocampal gyrus, and amygdala (Catani et al ; Schmahmann et al, ). The ILF tract bilaterally has been linked to a range of visual functions such as object recognition, visual learning, and face processing (Catani et al, ; Hodgetts et al, ; Ortibus et al, ; Ross, ). The left ILF, specifically, is a component of the ventral reading pathway that transmits information between the visual word form area (VWFA), located within the fusiform gyrus, and the anterior and medial temporal lobe (Epelbaum et al, ; Wandell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ILF pathway is generally considered a pathway through which information is conveyed from the extrastriate occipital cortex to the lateral temporal cortex, parahippocampal gyrus, and amygdala (Catani et al ; Schmahmann et al, ). The ILF tract bilaterally has been linked to a range of visual functions such as object recognition, visual learning, and face processing (Catani et al, ; Hodgetts et al, ; Ortibus et al, ; Ross, ). The left ILF, specifically, is a component of the ventral reading pathway that transmits information between the visual word form area (VWFA), located within the fusiform gyrus, and the anterior and medial temporal lobe (Epelbaum et al, ; Wandell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐known from monkey tract tracing studies that fusiform cortex provides substantial input to PRC (Suzuki & Naya, ), and multiple lines of research point to the importance of this pathway for object and face memory. In humans, recent work has shown that individual variability in the ability to remember unique faces is associated with the microstructural integrity of the inferior longitudinal fasciculus (Gomez et al, ; Hodgetts et al, ; Tavor et al, ; Unger, Alm, Collins, O'Leary, & Olson, ), which connects the fusiform gyrus with the ventral ATLs and PRC (Catani, Jones, Donato, & Ffytche, ; Pyles, Verstynen, Schneider, & Tarr, ).…”
Section: Discussionmentioning
confidence: 99%
“…The odd‐one‐out task was identical to that used in Shine et al () and Hodgetts et al (). Participants were shown three stimuli from the same visual category on each trial and instructed to select the stimulus that was the “odd‐one‐out” as quickly and as accurately as possible.…”
Section: Methodsmentioning
confidence: 99%
“…The statistical threshold for the fMRI analysis was voxel‐wise, uncorrected at p < 0.01 (as in Hodgetts et al, ). To prevent false positives due to multiple‐comparisons (as there were approximately 4,000 fMRI voxels within each PCu/PCC MRS metabolite group mask), Monte‐Carlo simulation was used to determine whether the size of any resulting cluster was statistically significant, using the 3dClustSim command in AFNI (2016 version, in which the bug identified in Eklund et al () had been fixed, https://afni.nimh.nih.gov/pub/dist/doc/program_help/3dClustSim.html).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation